Digestive Enzymatic Activity and Nutritional Responses of Helicoverpa armigera(Lepidoptera: Noctuidae) Larvae Fed Various Tomato Cultivars. Issue 4 (13th September 2014) - Naseri, B.; Kouhi, D.; Razmjou, J.; Golizadeh, A.
Abstract : Digestive enzymatic activity and nutritional responses of sixth-instar larvae of the tomato fruit borer, Helicoverpa armigera (Hübner), were studied on eight tomato cultivars commonly cultivated in Iran. Among various tomato cultivars, the larvae fed on 'Cal JN3' (4.860 ± 0.092 U/mg) significantly showed the highest level of proteolytic activity. However, proteolytic activity of the larvae reared on 'Sun 6108 f1' (2.182 ± 0.161 U/mg) was significantly lower than those reared on Cal JN3, 'Korral, ' 'Rio grande UG, ' 'Super crystal, ' and 'CH falat'. Also, the larvae fed on Korral (0.170 ± 0.007 mU/mg) significantly had higher amylolytic activity than the other tomato cultivars. The pupal weight of H. armigera was significantly lower on Rio grande UG (0.208 ± 0.014 g), Sun 6108 f1 (0.216 ± 0.008 g), and Super strain B (0.229 ± 0.014 g) than Cal JN3 and CH falat. Because the larvae and pupae reared on Rio grande UG were lighter than those fed on the others, this cultivar can be suggested as the least suitable host for feeding of H. armigera . However, because the mean weight gain of the larvae, food consumption, and larval weight during feeding period were significantly highest on CH falat, it can be selected as suitable cultivar for feeding of the pest.